Nanoparticle stable foam for inhibiting spontaneous combustion of residual coal in goaf and preparation method thereof

By using nanoparticles to stabilize the foam and using composite surfactant, thickener and resistor systems, the problem of poor stability of traditional water-based foam is solved, and the long-term inhibition effect and efficient suppression of spontaneous combustion of coal in goaf is achieved.

CN119680144APending Publication Date: 2025-03-25GUIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411841187.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Traditional water-based foams have shortcomings in stability and long-term resistance effects, and cannot meet the practical application requirements of spontaneous combustion suppression of goaf coal.

Method used

Nanoparticles are used to stabilize the foam, which consists of a composite surfactant, a composite thickener, a resistor system and nanomagnesium hydroxide particles. A stable foaming agent is obtained by electronic stirring and ultrasonic treatment.

Benefits of technology

The long-term stability and long-lasting coverage effect of the foam are achieved, effectively inhibiting spontaneous combustion of coal, reducing the temperature of the coal body and the environment, reducing the contact between oxygen and the coal body, and significantly improving the resistance performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680144A_ABST
    Figure CN119680144A_ABST
Patent Text Reader

Abstract

The invention provides nano-particle stable foam for inhibiting spontaneous combustion of residual coal in a goaf and a preparation method thereof.The inhibition foam is composed of water and a foaming agent matrix, and preparation raw materials of the inhibition foam matrix comprise a composite surfactant, a composite thickening agent, a stopping agent system and nano-magnesium hydroxide particles, the composite surfactant comprises fatty alcohol polyoxyethylene ether sodium sulfate and sodium dodecyl benzene sulfonate; the composite thickening agent comprises xanthan gum and carboxymethyl cellulose; the stopping agent system comprises high-molecular water-absorbent resin and ammonium polyphosphate; the nanometer material is selected from an inorganic corrosion inhibitor magnesium hydroxide. The problems that traditional water-based foam is poor in stability, the liquid drainage speed is high under the gravity, the long-term inhibition effect is not achieved, the application requirement is not met, and the stabilization time of a water-soluble polymer does not meet the actual application requirement are solved. Belongs to the technical field of mine fire prevention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nano-particle stable foam for inhibiting spontaneous combustion of coal residue in goaf and a preparation method thereof, belonging to the technical field of mine fire prevention and extinguishing. Background Art

[0002] During the mining process, coal is exposed to oxygen for a long time, which increases the possibility of spontaneous combustion of coal. Mine fires caused by spontaneous combustion of coal waste coal resources, pollute the environment, cause casualties, and may even cause secondary disasters such as gas or coal dust explosions. At present, the means of preventing and controlling spontaneous combustion of coal in goafs include grouting, injection of inert gas, injection of fire-fighting gel or spraying of inhibitors. These methods have played a vital role in preventing and delaying spontaneous combustion of coal. However, these technologies still have some shortcomings, such as toxicity, poor fluidity, and high cost.

[0003] Foam fire prevention and extinguishing technology has low cost and excellent pipeline transportation performance. It has gradually been used in the suppression of coal spontaneous combustion in mines. This technology uses the fluidity of foam to transport water and inhibitors to places in the goaf where coal spontaneous combustion is prone to occur. Even if the foam is broken, the inhibitor can still cover the surface of the broken coal and play a role in continuously suppressing coal spontaneous combustion. However, foam is thermodynamically unstable. Traditional water-based foam has poor stability and drains quickly under gravity. It does not have long-term inhibition effect and does not meet application requirements. Water-soluble polymers can enhance foam stability by increasing the viscosity of the foam solution, but the stabilization time still does not meet actual application requirements.

[0004] To this end, the present invention provides a nano-particle stabilized foam for inhibiting spontaneous combustion of coal residue in goaf areas and a preparation method thereof. Summary of the invention

[0005] The present invention provides a nanoparticle stabilized foam for inhibiting spontaneous combustion of coal residue in goaf and a preparation method thereof, so as to solve the problems that traditional water-based foam has poor stability, fast liquid drainage speed under gravity, lacks long-term inhibitory effect, does not meet application requirements, and the stabilization time of water-soluble polymers does not meet actual application requirements.

[0006] In order to solve the above problems, it is proposed to use a nanoparticle-stabilized foam for inhibiting spontaneous combustion of coal residue in goaf, which is composed of a foaming agent matrix and water;

[0007] The foaming agent matrix is ​​prepared from the following raw materials in parts by mass:

[0008] 0.7-0.9 parts of composite surfactant, 0.6-0.8 parts of composite thickener, 0.4-0.6 parts of inhibitor system, 0.6-0.8 parts of nano magnesium hydroxide particles;

[0009] Wherein, the composite surfactant is sodium sulfate of fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate;

[0010] The composite thickener is xanthan gum and carboxymethyl cellulose;

[0011] The inhibitor system is a polymer water-absorbing resin and ammonium polyphosphate.

[0012] In the aforementioned nanoparticle-stabilized foam, the sodium fatty alcohol polyoxyethylene ether sulfate and sodium dodecylbenzene sulfonate are mixed in a mass ratio of 2:8.

[0013] In the aforementioned nanoparticle-stabilized foam, the xanthan gum and carboxymethyl cellulose are mixed in a mass ratio of 3:2.

[0014] In the aforementioned nanoparticle-stabilized foam, the polymer water-absorbing resin and ammonium polyphosphate are mixed in a mass ratio of 1:4.

[0015] The preparation method of the above-mentioned nanoparticle-stabilized foam comprises:

[0016] According to the proportion, the composite surfactant, the composite thickener, the inhibitor system and the nano magnesium hydroxide are added into the deionized water, and stirred and pre-dispersed by an electronic stirrer;

[0017] The dispersion is transferred into an ultrasonic cleaning machine for ultrasonic treatment to obtain a uniformly dispersed foaming agent containing nanoparticles.

[0018] The preparation method of the above-mentioned inhibitor system comprises:

[0019] The inorganic inhibitor ammonium polyphosphate is dissolved in deionized water, and a physical inhibitor polymer water-absorbing resin is added in a certain proportion to prepare an inhibitor system;

[0020] The solution of the inhibitor system was stirred and mixed for 1 h, and then allowed to stand for 12 h;

[0021] The inhibitor system was placed in a vacuum drying oven, dried at 40° C. to a constant weight, and ground and sieved to obtain an inhibitor system powder.

[0022] In the above preparation method, the polymer water-absorbing resin is composed of ammonium polyphosphate and polymer resin in a mass ratio of 4:1.

[0023] In the above preparation method, the electronic stirrer is used for pre-dispersion for 20 minutes at a speed of 300 r / min; the ultrasonic treatment is carried out for 120 minutes at a power of 60 W and a temperature of 30°C.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The main component of the foam liquid film is water. During the foam flow and diffusion process, the water is carried to the coal body. The water vaporizes under the action of high temperature, absorbs a large amount of heat from the fire zone, reduces the temperature of the coal body and the surrounding environment, and can quickly cool the coal body that has a temperature rise trend, effectively inhibiting the spontaneous combustion of the coal.

[0026] 2. Compared with surfactant-stabilized foam, nanoparticle-stabilized foam is more stable. This improvement in stability is related to the size, type, surface wettability of the nanoparticles, and the synergistic effect between the surface charge of the nanoparticles and the net charge of the surfactant. This improvement in stability means that the foam can cover the coal surface for a longer time and more effectively interrupt the contact between coal and oxygen, thereby inhibiting the spontaneous combustion of the coal.

[0027] 3. The polymer thickener gives the foam viscosity, and after the foam completely loses water and breaks, it will form an oxygen-isolating covering layer on the surface of the coal. This adhesion helps the foam to cover the surface of the coal for a long time, effectively isolating the contact between coal and oxygen, and plays a role in preventing and controlling the residual coal for a long time and delaying coal oxidation.

[0028] 4. The excellent fluidity of the foam enables it to penetrate into the pores of the coal. The specific surface area of ​​the nanoparticles is larger than that of ordinary particles, which enables the foam to effectively fill the tiny cracks in the coal and expel some of the oxygen in the coal. The foam has a certain viscosity and stays in the cracks of the coal, reducing the migration of oxygen in the cracks.

[0029] 5. The inorganic inhibitor ammonium polyphosphate decomposes into polyphosphoric acid when heated, releasing inflammable gases such as nitrogen and ammonia, diluting the oxygen in the air. At the same time, its pyrolysis process is an endothermic reaction, which can absorb the heat generated by the spontaneous combustion of coal, and synergize with the vaporization of water to absorb heat to lower the temperature of the coal body and reduce the heating rate of the coal, thereby inhibiting the spontaneous combustion of the coal.

[0030] 6. As a part of the inhibitor system, the polymer water-absorbing resin has high water absorption performance and can form a water film layer on the surface of the coal body to block the contact between oxygen and the coal body. This water absorption performance helps to keep the coal body moist, reduce the functional groups in the coal oxidation reaction, prevent free radical reactions, and inhibit the oxidation reaction rate.

[0031] The preparation method of the invention is simple, low in production cost, non-toxic and pollution-free, has good catalytic performance and strong promotion potential, which means that the technology is not only effective, but also economical, easy to apply on a large scale and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The CO concentration changes of the inhibitory foaming agents prepared for the blank control group, Example 1 and Comparative Examples 1-3 to inhibit the spontaneous combustion of coal;

[0033] Figure 2The inhibitory foaming agents prepared in the blank control group, Example 1 and Comparative Examples 1-3 inhibit changes in the O2 consumption rate of coal spontaneous combustion. DETAILED DESCRIPTION

[0034] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] Example 1

[0036] This embodiment provides a method for preparing a nanoparticle-stabilized foam for inhibiting spontaneous combustion of coal residue in goaf areas:

[0037] ① 0.79g of a composite surfactant, 0.79g of a composite thickener, 0.52g of an inhibitor system and 0.79g of nano-magnesium hydroxide particles were dissolved in 100g of deionized water to obtain a mixed foaming agent solution;

[0038] The inhibitor system has been ground in advance, the sodium fatty alcohol polyoxyethylene ether sulfate and sodium dodecylbenzene sulfonate in the composite surfactant are mixed at a mass ratio of 2:8, and the xanthan gum and carboxymethyl cellulose in the composite thickener are mixed at a mass ratio of 3:2.

[0039] Among them, the proportion is calculated as follows:

[0040] 0.158g sodium fatty alcohol polyoxyethylene ether sulfate, 0.632g sodium dodecylbenzene sulfonate, 0.474g xanthan gum, 0.316g carboxymethyl cellulose.

[0041] ②. Use an electronic stirrer to stir the mixture at a speed of 300 rpm for preliminary dispersion for 20 minutes;

[0042] ③. Transfer the dispersion into an ultrasonic cleaner and disperse for 120 minutes, set the power to 60W and the temperature to 30℃;

[0043] ④. After the above steps, a nano-particle-stabilized inhibitory foaming agent for preventing and controlling spontaneous combustion of coal residue in goaf is obtained.

[0044] Comparative Example 1

[0045] This comparative example provides a method for preparing a traditional water-based foaming agent for inhibiting spontaneous combustion of coal residue in goafs, which is composed of a foaming agent matrix and water. The matrix is ​​prepared from 0.79 parts of a composite surfactant as a raw material in parts by mass.

[0046] The sodium fatty alcohol polyoxyethylene ether sulfate and sodium dodecylbenzene sulfonate in the composite surfactant are mixed in a mass ratio of 2:8;

[0047] The foaming agent of this comparative example is prepared by the following steps:

[0048] 0.158 g of sodium fatty alcohol polyoxyethylene ether sulfate and 0.632 g of sodium dodecylbenzene sulfonate are directly mixed with 100 g of water and stirred evenly to obtain a conventional water-based foam foaming agent for inhibiting spontaneous combustion of coal left in goaf.

[0049] That is to say, the difference between this comparative example and Example 1 is:

[0050] In this comparative example, when preparing the water-based foam blowing agent, only the composite surfactant is added, and the next step of adding the base is not performed.

[0051] Comparative Example 2

[0052] This comparative example provides a method for preparing a polymer stabilized foaming agent for inhibiting spontaneous combustion of coal residue in goaf areas, which is composed of a foaming matrix and water, wherein the matrix is ​​prepared from 0.79 parts of a composite surfactant and 0.79 parts of a composite thickener in parts by mass;

[0053] The xanthan gum and carboxymethyl cellulose in the composite thickener are mixed in a mass ratio of 3:2;

[0054] 0.158g of sodium fatty alcohol polyoxyethylene ether sulfate, 0.632g of sodium dodecylbenzene sulfonate and 100g of water are mixed and stirred evenly, and then 0.474g of xanthan gum and 0.316g of carboxymethyl cellulose are added thereto, mixed and stirred evenly to obtain a polymer-stabilized foam foaming agent for inhibiting spontaneous combustion of coal left in goafs.

[0055] That is to say, the difference between this comparative example and Example 1 is:

[0056] In this comparative example, when preparing the polymer-stabilized foaming agent, a composite surfactant and a composite thickener were added, but no inhibitor system and nano-magnesium hydroxide particles were added.

[0057] Comparative Example 3

[0058] This comparative example provides a method for preparing an inorganic inhibitor foaming agent for inhibiting spontaneous combustion of coal left in goaf, which is composed of a foaming matrix and water. The matrix is ​​prepared from 0.79 parts of a composite surfactant, 0.79 parts of a composite thickener and 0.52 parts of an inhibitor system by weight.

[0059] 0.158g of sodium fatty alcohol polyoxyethylene ether sulfate, 0.632g of sodium dodecylbenzene sulfonate and 100g of water are mixed and stirred evenly, then 0.474g of xanthan gum and 0.316g of carboxymethyl cellulose are added thereto and stirred evenly, and then 0.52g of inhibitor system is added thereto, mixed and stirred evenly to obtain an inorganic inhibitor foam foaming agent for inhibiting spontaneous combustion of coal left in goaf.

[0060] That is to say, the difference between this comparative example and Example 1 is only that:

[0061] In this comparative example, nano magnesium hydroxide particles were not added and ultrasonic treatment was not performed.

[0062] Experimental Section

[0063] ①. Preparation of experimental coal samples

[0064] A certain amount of lignite is crushed, and the crushed coal samples are sieved into two particle sizes of 60-80 mesh and 80-100 mesh using sieves with mesh sizes of 60 mesh, 80 mesh and 100 mesh. The coal samples of these two particle sizes are then mixed in a 1:1 ratio of equal mass to obtain the experimental coal samples.

[0065] ②. Preparation of experimental samples

[0066] The present invention takes 20g of the foaming inhibitor prepared in Example 1 and Comparative Examples 1-3, respectively, mixes them evenly with 20g of the experimental coal samples prepared above, and soaks and preserves them for 24 hours as the experimental group; another 20g of the experimental coal samples prepared above (without adding any reagents) is taken, sealed and preserved for 24 hours as the blank control group.

[0067] After 24 hours, the coal samples of the experimental combination control group were placed in a vacuum drying oven and vacuum dried at 30°C for 48 hours. The coal samples were then sealed and stored for the next experiment.

[0068] Among them, there are 4 experimental groups, which are experimental coal samples treated with foaming agents of comparative examples 1-3 and embodiment 1, and are named experimental group 1, experimental group 2, experimental group 3 and experimental group 4 respectively; the blank control group without inhibitor treatment is named original sample group.

[0069] The present invention conducts programmed temperature experiments on the samples of the above experimental groups 1-4 and the samples of the original sample group to analyze the O2 consumption rate of the coal samples and the inhibitory properties of the inhibitor on the coal samples.

[0070] Programmed temperature experiment: put the sample to be tested into the experimental coal sample tank, set the gas flow value to 100ml / min, and check the air tightness of the entire equipment; set the heating temperature range to 30-280℃, and the heating rate to 0.8℃ / min. When the coal temperature rises to 30℃, start collecting gas and analyze it using a gas chromatograph.

[0071] The sample was heated by a programmed temperature experiment, and the gas release at different temperatures was analyzed by a gas chromatograph to draw a CO concentration change curve ( Figure 1 ), draw the rate change curve of coal sample consumption Q2 at different temperatures ( Figure 2), and the inhibition rate of different inhibitors on coal samples was calculated according to the CO release amount corresponding to 100℃ (Table 2).

[0072] The calculation formula of the resistance rate I is:

[0073]

[0074] In the above formula:

[0075] I is the resistance rate, in %;

[0076] Q1 is the CO concentration produced by the raw coal sample at 100°C, in ppm;

[0077] Q2 is the CO concentration produced by the quenched coal sample at 100°C, in ppm;

[0078] Table 1 CO concentration generated by each sample at 100℃

[0079] Test samples Blank control group Experimental Group 1 Experimental Group 2 Experimental Group 3 Experimental Group 4 CO / ppm 476.672 351.02 326.825 230.592 140.038

[0080] Table 2 Resistance test results

[0081] Test samples Experimental Group 1 Experimental Group 2 Experimental Group 3 Experimental Group 4 Inhibition rate / % 26.36 31.44 51.62 70.61

[0082] According to requirement 4.1 of "General Technical Conditions for Inhibitors for Coal Mine Fire Prevention MT / T 700-2019", the group rate of the inhibitor should not be less than 40%.

[0083] The calculation formula of O2 consumption rate is:

[0084]

[0085] In the above formula:

[0086] is the oxygen consumption rate, in mol / (cm 3 s);

[0087] C0 is the standard oxygen volume fraction, in mol / cm 3

[0088] S is the cross-sectional area of ​​the furnace body in the coal sample tank. The cross-sectional area of ​​the furnace body used in the present invention is 4.71 cm 2 ;

[0089] L is the height of the coal body in the coal sample tank, which is 6.3 cm;

[0090] Q is the gas flow rate, which is 100 ml / min;

[0091] and are the O2 concentrations at the inlet and outlet, in mol / cm 3 ;

[0092] The above formula is used to calculate the O2 consumption rate of each coal sample at different temperatures, such as Figure 2 shown.

[0093] The programmed temperature test was carried out on the raw coal sample groups of Experiment 1-4. CO gas appears early in the coal spontaneous combustion process, and its production and concentration growth rate are relatively large. It is one of the main indicator gases of early coal spontaneous combustion and also a key parameter of coal oxidation kinetics. From Table 2 and Figure 1 It can be seen that by analyzing the changes in CO concentration of the coal samples in the embodiments, comparative examples and original coal samples and the inhibition rate of different foaming agents on the coal samples, it was found that the coal samples treated with nanoparticle-stabilized foam produced the least CO and had the highest inhibition rate.

[0094] The oxygen consumption rate curves of different coal samples with temperature are as follows: Figure 2 As shown. The oxygen consumption rate of each coal sample increases with the increase of temperature, and there is a critical mutation point in the change stage, which means that the coal oxygen has entered a rapid oxidation stage. The oxygen consumption rate of the coal samples in the control group and experimental group 1 increased sharply after 110°C. The oxygen consumption rate of the coal samples in experimental groups 2 and 3 began to increase sharply after 130°C. The coal samples treated with nanoparticle-stabilized foam began to increase sharply after 140°C, and the oxygen consumption rate was always the lowest.

[0095] From the CO concentration change, the inhibition rate and the O2 consumption rate, it can be seen that the inhibition effect of each foaming agent is ranked from small to large as follows: traditional water-based foam < polymer stabilized foam < inhibition foam < nanoparticle stabilized foam. The material for inhibiting spontaneous combustion of coal in goafs of the present invention is mainly based on the synergistic effect of the group-chemical system and nanoparticles, which can achieve the effects of inhibiting CO production, isolating O2 and cooling the target coal body. In addition, the preparation method of this foam material is simple and efficient.

[0096] Obviously, the above-mentioned embodiments and comparative examples are only a part of the present invention, rather than all examples. The preferred embodiments of the present invention disclosed above are only used to help explain the present invention, without describing all the details in detail. According to the content of this specification, more modifications and changes can be made. Based on the embodiments and comparative examples in the present invention, all other embodiments and various modifications or supplements obtained by ordinary technicians in the field without making creative work, as long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, belong to the scope of protection of the present invention.

[0097] In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiments and comparative examples. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments in a suitable manner.

Claims

1. A nanoparticle-stabilized foam for inhibiting spontaneous combustion of coal in goaf, characterized in that: It consists of a foaming agent matrix and water; The foaming agent matrix is ​​prepared from the following raw materials in parts by mass: 0.7-0.9 parts of composite surfactant, 0.6-0.8 parts of composite thickener, 0.4-0.6 parts of inhibitor system, 0.6-0.8 parts of nano magnesium hydroxide particles; Wherein, the composite surfactant is sodium sulfate of fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate; The composite thickener is xanthan gum and carboxymethyl cellulose; The inhibitor system is a polymer water-absorbing resin and ammonium polyphosphate.

2. The nanoparticle-stabilized foam for inhibiting spontaneous combustion of coal in goaf according to claim 1, characterized in that: The sodium fatty alcohol polyoxyethylene ether sulfate and sodium dodecylbenzene sulfonate are mixed in a mass ratio of 2:

8.

3. The nanoparticle-stabilized foam for inhibiting spontaneous combustion of coal in goaf according to claim 1, characterized in that: The xanthan gum and carboxymethyl cellulose are mixed in a mass ratio of 3:

2.

4. The nanoparticle-stabilized foam for inhibiting spontaneous combustion of coal in goaf according to claim 1, characterized in that: The polymer water-absorbing resin and ammonium polyphosphate are mixed in a mass ratio of 1:

4.

5. The method for preparing the nanoparticle-stabilized foam according to any one of claims 1 to 4, characterized in that: The following steps are involved: According to the proportion, the composite surfactant, the composite thickener, the inhibitor system and the nano magnesium hydroxide are added into the deionized water, and stirred and pre-dispersed by an electronic stirrer; The dispersion is transferred into an ultrasonic cleaning machine for ultrasonic treatment to obtain a uniformly dispersed foaming agent containing nanoparticles.

6. The preparation method according to claim 5, characterized in that: The method for preparing the inhibitor system comprises the following steps: The inorganic inhibitor ammonium polyphosphate is dissolved in deionized water, and a physical inhibitor polymer water-absorbing resin is added in a certain proportion to prepare an inhibitor system; The solution of the inhibitor system was stirred and mixed for 1 h, and then allowed to stand for 12 h; The inhibitor system was placed in a vacuum drying oven, dried at 40° C. to a constant weight, and ground and sieved to obtain an inhibitor system powder.

7. The preparation method according to claim 6, characterized in that: The polymer water-absorbing resin is composed of ammonium polyphosphate and polymer resin in a mass ratio of 4:

1.

8. The preparation method according to claim 5, characterized in that: The electronic stirrer was used for pre-dispersion for 20 min at a speed of 300 r / min; ultrasonic treatment was performed for 120 min at a power of 60 W and a temperature of 30°C.